Additive-treated corn silage for growing cattle - K. Bolsen; R. Smith; H. Ilg; D. Axe (Kansas Agricultural Experiment Station Research Reports, 1986)
The response of corn silage to the additive, Silo-Best Soluble®, was not consistent for the farm silo criteria measured. Ensiling temperatures and chemical compositions were similar for control and treated silages, except for ethanol, which was lower in the treated silage. Dry matter recovery favored the treated silage in both the top and bottom halves of the silos and in buried bags. Although daily gains were similar for calves fed control and treated silages, feed conversion was slightly better for those fed control silage.
Keywords: Cattlemen& #x27; s Day; 1986; Kansas Agricultural Experiment Station contribution; no. 86-320-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 494; Beef; Corn silage; Growing cattle